Mineralogical Crystallography - Gurzhiy, Vladislav V. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Crystallography remains, for mineralogy, one of the main sources of information on natural crystalline substances. A description of mineral species shape is carried out according to the principles of geometric crystallography; the crystal structure of minerals is determined using X-ray crystallography techniques, and physical crystallography approaches allow one to evaluate various properties of minerals, etc. However, the reverse comparison should not be forgotten as well: the crystallography science, in its current form, was born in the course of mineralogical research, long before preparative chemistry received such extensive development. It is worth noting that, even today, investigations of crystallographic characteristics of minerals regularly open up new horizons in materials science, because the possibilities of nature (fascinating chemical diversity; great variation of thermodynamic parameters; and, of course, almost endless processing time) are still not available for reproduction in any of the world's laboratories. This Special Issue is devoted to mineralogical crystallography, the oldest branch of crystallographic science, and aims to combine important surveys covering topics indicated in the keywords below.